Renewable Agriculture and Food Systems, (Formerly: American Journal of Alternative Agriculture) (Cambridge University Press)
This is a multi-disciplinary journal which focuses on the science that underpins economically, environmentally and socially sustainable approaches to agricluture and food production.
Keywords: Agriculture and Food Production